2001
DOI: 10.1080/10256010108033294
|View full text |Cite
|
Sign up to set email alerts
|

Food Web Implications of δ13C and δ15N Variability over 370 km of the Regulated Colorado River USA

Abstract: Dual stable isotope analysis in the regulated Colorado River through Grand Canyon National Park, USA, revealed a food web that varied spatially through this arid biome. Down-river enrichment of delta13C data was detected across three trophic levels resulting in shifted food webs. Humpack chub delta13C and delta15N values from muscle plugs and fin clips did not differ significantly. Humpback chub and rainbow trout trophic position is positively correlated with standard length indicating an increase in piscivory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
5
20
2
Order By: Relevance
“…The minimal influence of dams on the d 13 C values of potential food sources and biota in this study is in contrast to other studies that have demonstrated enrichment or depletion of 13 C in biota downstream of dams (Angradi 1993(Angradi , 1994Shannon et al 2001;Doi et al 2008). The influence of the Lostock and Chichester dams on downstream d…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The minimal influence of dams on the d 13 C values of potential food sources and biota in this study is in contrast to other studies that have demonstrated enrichment or depletion of 13 C in biota downstream of dams (Angradi 1993(Angradi , 1994Shannon et al 2001;Doi et al 2008). The influence of the Lostock and Chichester dams on downstream d…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, Angradi (1994) observed depletion of 13 C and 15 N in seston in a downstream direction and no longitudinal variation in the isotopic composition of amphipods or fish for 25 km. Shannon et al (2001) observed enrichment of 13 C in benthic algae, macroinvertebrates and fish up to 350 km downstream of Glen Canyon Dam but no longitudinal trends in d 15 N for the same groups. Doi et al (2008) used isotope signatures of phytoplankton to suggest that they contributed to the downstream food webs for up to 10 km.…”
Section: Introductionmentioning
confidence: 88%
“…Many studies suggested widespread correlations between fish size and habitat use and feeding (e.g. Minns 1995, Gu et al 1996, Shannon et al 2001, Barnes et al 2008, Chassot et al 2008), but fish size was not a major influence in our study. The influence of size may decline with increasing complexity of food webs where body size of primary consumer taxa is highly variable (Layman et al 2005).…”
Section: Variation In Stable Isotope Valuesmentioning
confidence: 53%
“…Stable isotopic values often vary with body size (Gu et al 1996, Shannon et al 2001, Barnes et al 2008, so log transformed length was included as a covariate in tests for site differences in δ N stable isotope values between sites were evaluated using circular statistics with Oriana (Schmidt et al 2007). Such analysis uses Rayleigh's Z statistic.…”
Section: Methodsmentioning
confidence: 99%
“…The method of comparing non-destructive and destructive tissue in animals for stable isotope research has yielded successful results with fish (Shannon et al 2001;Johnson et al 2002;Jardine et al 2005;Kelly et al 2006;Sanderson et al 2009), birds , and sea turtles (Seminoff et al 2006), and this study shows this method can work well with other ectothermic vertebrates. Though our results suggest species-specific differences in stable isotope relationships among tissues, we caution that our study cannot resolve whether there were truly species-specific differences.…”
Section: Discussionmentioning
confidence: 89%